Absence of Nitrergic Modulation of Starling Response in Haemoglobin-Less Antarctic Fish Chionodraco hamatus - Amelio D.; Garofalo F.; Brunelli E.; Santovito G.; Pellegrino D. (Journal of Marine Science and Engineering, 2022)
The Frank-Starling response is an intrinsic heart property that is particularly evident in the fish heart because piscine cardiomyocytes are extremely sensitive to stretch. Several mechanisms and compounds influence the Frank-Starling response, including the free radical nitric oxide produced by nitric oxide synthases in the vascular endothelium and cardiomyocytes of all vertebrates. Besides its role in scavenging nitric oxide, hemoglobin may act as a source and transporter. In this context, the hemoglobin-less Antarctic teleost Chionodraco hamatus (icefish) represents a unique opportunity to investigate the involvement of nitric oxide in the Frank-Starling response. Using an isolated perfused heart preparation, weverified a basal nitrergic tone that is not implicated in the Frank-Starling response. In addition, by comparing nitric oxide synthases expression and activation in C. hamatus and the red-blooded Antarctic teleost Trematomus bernacchii, we found the endothelial isoform of nitric oxide synthase (the primary generator of nitric oxide during shear stress) to be less expressed and activated in the former.